Electromagnetic Model for Determining the Speed of Absorptive Photonic in a Solar Collector in V (V-Collector) (2017)
The electromagnetic model for determining the speed of absorptive photonic in a V-collector was developed as the function of electrical and magnetic characteristics of a medium, considering both the phase factors and the attenuation of the suspension. For this purpose the six-flux model was used to simulate the photonic absorption and the ray-tracing tool was used to model the rays of incident radiation on the V-collector. The developed model represents a new approach to those reported previously in the literature..